Defects in T Cell Trafficking and Resistance to Cancer Immunotherapy - Donnadieu, Emmanuel (Resistance to Targeted Anti-Cancer Therapeutics,, 2016)
This volume focuses on recent advances in understanding T cells as key players in antitumor immune responses, and as a result T cell-based immunotherapy is starting to transform the treatment of advanced cancers. However, despite recent successes, many patients with cancer fail to respond to these treatments. Defective migration of T cells into and within tumors is considered as an important resistance mechanism to cancer immunotherapy. The volume includes three sections. The first section covers general knowledge about T cell trafficking during a normal immune response but also during tumor development. The second section provides an in-depth description of the different obstacles that prevent T cells from migrating and contacting tumor cells. The third section explores therapeutic strategies to improve trafficking of T cells into tumors and, thus, to enhance the effectiveness of cancer immunotherapy.